Pengaruh Store Atmosphere Terhadap Customer Dwell time Pada Revo Mall Bekasi - Gavin Aulia Razan; Evi Selvi (Journal of Management and Creative Business, 2026)
This study aims to examine the effect of Store Atmosphere on Customer Dwell time at Revo Mall Bekasi. A quantitative approach was employed involving 100 respondents selected through purposive sampling. Data were analyzed using IBM SPSS through validity, reliability, normality, heteroscedasticity, simple linear regression, t-test, F-test, and coefficient of determination analyses. The results indicate that the research instruments are valid and reliable, the data are normally distributed, and no heteroscedasticity is detected. The t-test and F-test show that Store Atmosphere has a positive and significant effect on Customer Dwell time with a significance value of 0.000 (<0.05). The coefficient of determination (R²) of 0.754 indicates that Store Atmosphere explains 75.4% of the variation in Customer Dwell time, while the remaining 24.6% is influenced by other factors outside the scope of this study. Therefore, a better Store Atmosphere leads to longer Customer Dwell time at Revo Mall Bekasi.